1993
DOI: 10.1164/ajrccm/147.1.211
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pneumonia in Mechanically Ventilated Patients: Repeatability of the Protected Specimen Brush

Abstract: The repeatability (i.e., the variation in repeated measurements of the same quantity) of the protected specimen brush (PSB) with quantitative cultures was assessed in 22 consecutive mechanically ventilated (MV) patients with suspected nosocomial pneumonia. Five PSB samples were collected in the same lung area during the same bronchoscopic procedure and processed for bacteriologic identification and quantitative culture. A laboratory control was also performed in order to assess the in vitro repeatability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…However, studies investigating the reproducibility and variability of bronchoscopic PSB have raised concerns about this technique. Timsit et al and Marquette et al repeated PSB sampling in the same lung subsegment and noted that results of quantitative cultures were on each side of the 10 3 -CFU/ml threshold in 16.7% to 13.6% of cases, respectively, with 59 to 67% of samples having CFU/ml counts varying by more than 10-fold (131,196). These investigators concluded that, as with all quantitative culturing techniques, borderline PSB quantitative culture results should be interpreted with caution.…”
Section: Microbiologic Diagnosismentioning
confidence: 99%
“…However, studies investigating the reproducibility and variability of bronchoscopic PSB have raised concerns about this technique. Timsit et al and Marquette et al repeated PSB sampling in the same lung subsegment and noted that results of quantitative cultures were on each side of the 10 3 -CFU/ml threshold in 16.7% to 13.6% of cases, respectively, with 59 to 67% of samples having CFU/ml counts varying by more than 10-fold (131,196). These investigators concluded that, as with all quantitative culturing techniques, borderline PSB quantitative culture results should be interpreted with caution.…”
Section: Microbiologic Diagnosismentioning
confidence: 99%
“…MARQUETTE et al [13] found a 13.6% discordance in quantitative bacterial results, but there was a noticeable intrasubject variability (16%). TIMSIT et al [11] found similar results with a 24% discordance with regard to the recommended diagnostic threshold of 10 3 cfu?mL -1 .…”
Section: Discussionmentioning
confidence: 95%
“…PSB was first described by WIMBERLEY et al [8]. The transection of the PSB has been reported to be performed either at bedside [9 -11] or in the laboratory [12,13], where all the microbiological processing will be finally done. It may be assumed that differences in this procedure may influence the microbiological results.…”
mentioning
confidence: 99%
“…Two studies [42,43] have found that a repeated PSB sampling in the same segmental area had a clear degree of variability, with 14% of culture spreading above and below the 10 3 cfu . mL -1 threshold in one study [42] and 40% of spreading in the other [43]. Finally, a bacterial bronchiolitis without pneumonia could also provide a false-negative result.…”
Section: Bronchoscopic Techniquesmentioning
confidence: 99%
“…The variability of the technique could provide also false-positive results. MARQUETTE et al [42] reported that 60% of patients had PSB results that varied by more than one log unit when ®ve PSB samplings were performed in the same patients and site. The bacterial colonization of the lower airways is frequent in patients with chronic obstructive pulmonary disease (COPD), bronchiectasis or prolonged antibiotic treatment, resulting in false-positive results of the sample obtained by PSB.…”
Section: Bronchoscopic Techniquesmentioning
confidence: 99%